Kadar Plasma 25-Hydroxyvitamin-D (25-OHD) pada Pasien Age-related Macular Degeneration (AMD) Stadium Akhir di Yogyakarta: Studi Korelasi - Supanji Supanji; Dewi Fathin Romdhoniyyah; Ayudha Bahana Ilham Perdamaian; Anindita Dianratri; Muhammad Bayu Sasongko; Angela Nurini Agni; Tri Wahyu Widayanti; Firman Setya Wardhana; Dian Caturini Sulistyaningrum; Mohammad Eko Prayogo; Masashi Kawaichi; Chio Oka (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Age-related Macular Degeneration (AMD) is a degenerative disease caused by multiple factors, including inflammation. This condition may lead to irreversible macular damage. Vitamin D has anti-inflammatory and immune-modulating qualities, therefore, is expected to protect against the development of AMD.Objective: This study aimed to evaluate the correlation between plasma 25-hydroxyvitamin D (plasma 25-OHD) levels and neovascular Age-Related Macular Degeneration (nAMD).Methods: This was a case-control study involving AMD and control subjects. All subjects underwent a standardized eye examination to check for eligibility by a retinal specialist. Blood samples were drawn for analysis using a DRG Elisa Kit to determine the plasma 25-OHD (Total). Plasma 25-OHD levels were categorized into deficiency (<12 ng/mL), insufficiency (12 - <20 ng/mL), adequate (20 – 50 ng/mL), and high (>50 ng/mL).Results: Total subjects were 39, which consisted of 20 AMD subjects and 19 controls. There were 17 male subjects (43.6%) and 22 female subjects (56.4%). The mean age for the case and control group was 69.35±7.04 and 68.26±6.83, respectively (p=0.612). Those in their 70s dominated the age distribution with a percentage of 56.41% of all participants. The mean plasma 25-OHD in the case group was 32.30±17.10 ng/mL, while the control group was 50.63±11.95 ng/mL (p=0.066). There was no significant association between AMD and plasma 25-OHD levels in all groups (p>0.05).Conclusion: Plasma 25-OHD levels did not correlate positively with nAMD in our study population.